Cultural Negotiation through Food Case study: Chinese Soft Diplomacy in Indonesia - Amorisa Wiratri (Kawalu: Journal of Local Culture, 2017)
Abstract Food is one of the common ways for one culture to penetrate another culture through migrants. Chinese migrants in Indonesia have introduced their food culture to Indonesians for some centuries and now Indonesians might find it difficult to recognize whether they are now local, fusion or Chinese food. The acceptance of Chinese food in Indonesia serves an example on how soft diplomacy and culture negotiation has completely succeeded. Chinese food has already blended with Indonesian culture and Indonesians nowadays are acquainted with. This study will use literature as main resources. Historical and anthropological approach will be used in analyzing the data. This paper tries to focus on three mains issues, which are the history of Chinese migration in Indonesia, the history and acculturation of Chinese food in Indonesia and culture negotiation through food. In conclusion, the acceptance of Chinese food in Indonesia culture is part of the success of soft diplomacy and culture negotiation between Chinese migrants and Indonesian leads to the permission of other form of diplomacy.